2022
DOI: 10.3389/fnut.2022.874943
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Serum Biomarkers of Fruit and Vegetable Intake With the Risk of Cause–Specific Mortality and All–Cause Mortality: A National Prospective Cohort Study

Abstract: ObjectiveThe purpose of this study was to evaluate the associations of serum biomarkers of fruit and vegetable intake (vitamin C and carotenoids) with cause–specific mortality and all–cause mortality in a nationally representative sample of US adults.MethodsWe analyzed data from 12,530 participants from the National Health and Nutrition Examination Survey III (1988–1994). The Cox proportional hazards models with restricted cubic spline were used for the analysis.ResultsDuring 246,027 person–years of follow–up,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…[34][35][36] In addition, dietary antioxidants can protect against oxidative stress and the harmful effects of reactive oxygen species 37 and have been reported to inhibit the proliferation of human cancer cells 38 and decrease cancer mortality. 39,40 Second, a healthy plant-based diet could promote the gut microbial environment, the "gut-lung axis," which suggests that the gut microbiota can affect the lungs through local and systemic immune responses. 41 Previous studies have suggested that the gut microbiota significantly affects the efficacy of tumor immunotherapy.…”
Section: Food and Function Papermentioning
confidence: 99%
“…[34][35][36] In addition, dietary antioxidants can protect against oxidative stress and the harmful effects of reactive oxygen species 37 and have been reported to inhibit the proliferation of human cancer cells 38 and decrease cancer mortality. 39,40 Second, a healthy plant-based diet could promote the gut microbial environment, the "gut-lung axis," which suggests that the gut microbiota can affect the lungs through local and systemic immune responses. 41 Previous studies have suggested that the gut microbiota significantly affects the efficacy of tumor immunotherapy.…”
Section: Food and Function Papermentioning
confidence: 99%